Fangchinoline Induces G1 Arrest in Breast Cancer Cells Through Cell‐Cycle Regulation. (11th February 2013) - Xing, Zhibo; Zhang, Youxue; Zhang, Xianyu; Yang, Yanmei; Ma, Yuyan; Pang, Da
<x xml:space="preserve">Abstract</x> Fangchinoline, an alkaloid derived from the dry roots of Stephaniae tetrandrine S. Moore (Menispermaceae), has been shown to possess cytotoxic, anti‐inflammatory, and antioxidant properties. In this study, we used Fangchinoline to inhibit breast cancer cell proliferation and to investigate its underlying molecular mechanisms. Human breast cancer cell lines, MCF‐7 and MDA‐MB‐231, were both used in this study. We found that Fangchinoline significantly decreased cell proliferation in a dose‐dependent manner and induced G1‐phase arrest in both cell lines. In addition, upon analysis of expression of cell cycle‐related proteins, we found that Fangchinoline reduced expression of cyclin D1, cyclin D3, and cyclin E, and increased expression of the cyclin‐dependent kinase (CDK) inhibitors, p21/WAF1, and p27/KIP1. Moreover, Fangchinoline also inhibited the kinase activities of CDK2, CDK4, and CDK6. These results suggest that Fangchinoline can inhibit human breast cancer cell proliferation and thus may have potential applications in cancer therapy. Copyright © 2013 John Wiley & Sons, Ltd.